Teacher questioning strategies in the mathematics classroom - Wong, Elaine (Nanyang Technological University, 2021)
Teaching questioning is significant to effective mathematical classroom discourse (Koizumi, 2013; McCarthy, Sithole, McCarthy, Cho Gyan, 2016). Questioning, as an instrument of teaching, is able to challenge students' thinking and motivate their learning processes (Shahrill & Clarke, 2014). When teachers are aware of the questioning strategies they use, it facilitates teacher-student interactions imminent to learning (McCarthy et al., 2016). This study explores the types of questions used by the teacher(s) in Mathematics classroom. [1st Award]